Keadilan Restoratif sebagai Dasar Penghentian Penuntutan oleh Jaksa dalam Perspektif Hak Asasi Manusia - Ahmadi, Iqbal Risha; Suteki (Yuriska: Jurnal Ilmiah Hukum, 2021)
Background: The shift in the concept of retributive justice to restorative justice has also been realized and felt by the Prosecutor’s Office of the Republic of Indonesia as the institution authorized to prosecute in criminal cases. So far, the concept of retributive justice in criminal law enforcement has not been proven optimally and effectively in tackling and controlling crime. In fact, in practice it often causes injustice that violates human rights. Research methods: This article is a descriptive study with a normative juridical approach that examines the literature on secondary data sources. Research result: The results obtained are, as a manifestation of the active role of the Prosecutor’s Office of the Republic of Indonesia in carrying out its duties and authorities, namely law enforcement and respect for human rights, the Attorney General has issued Attorney General Regulation No. 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. Conclusion: The implementation of the termination of prosecution is based on the principles that provide protection of human rights, namely the principle of justice, the principle of public interest, the principle of proportionality, the principle of ultimum remedium and the principle of quick, simple and low-cost justice. Of course, this also needs to be supported by a prosecutor with integrity, professional, progressive and not limited by written rules with the ability to explore the laws that live in society by adhering to values ​​that uphold human rights contained in Pancasila and the 1945 Constitution.